2015
DOI: 10.1159/000440986
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Associated Acute Kidney Injury and Long-Term Cardiovascular Outcomes

Abstract: Background: Acute kidney injury (AKI) has been associated with all-cause short- and long-term mortality. However, its association with cardiovascular (CV) events remains unclear. We sought to investigate this in patients undergoing open (OAR) or endovascular (EVAR) abdominal aortic aneurysm repair, as they are likely to develop both AKI and CV morbidity. A meta-analysis was subsequently performed to confirm this in other CV-interventions. Methods: AKI-incidence was assessed in a multicentre-cohort of 1,068 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 45 publications
5
52
0
Order By: Relevance
“…A study involving 10,518 patients undergoing surgery suggested that long-term survival was worse those with AKI, even after complete eGFR recovery (43). We have previously shown a strong association between AKI after endovascular intervention, vascular surgery, renal transplantation or coronary angiography and subsequent short and longterm cardiovascular events and all-cause morbidity, in multiple cohort studies as well as a metaanalysis (4,26,28,29). A recent review from NICE suggests that AKI has a major impact on safety and healthcare-cost (44); a patient with AKI after intervention spends an average of 4.7 extra nights hospitalised with an additional £3,691 for medical-treatment (5,44).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…A study involving 10,518 patients undergoing surgery suggested that long-term survival was worse those with AKI, even after complete eGFR recovery (43). We have previously shown a strong association between AKI after endovascular intervention, vascular surgery, renal transplantation or coronary angiography and subsequent short and longterm cardiovascular events and all-cause morbidity, in multiple cohort studies as well as a metaanalysis (4,26,28,29). A recent review from NICE suggests that AKI has a major impact on safety and healthcare-cost (44); a patient with AKI after intervention spends an average of 4.7 extra nights hospitalised with an additional £3,691 for medical-treatment (5,44).…”
Section: Discussionmentioning
confidence: 96%
“…Acute Kidney Injury (AKI) occurs in 13-18% of all hospital admissions and 20% of patients undergoing intervention (1)(2)(3)(4)(5)(6). Development of AKI (7,8) has been associated over both the short and long-term with increased rates of morbidity, hospital-stay, treatment-cost, and mortality (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations